Hubungan antara Dukungan Keluarga dengan Motivasi Belajar Peserta Didik Paket B di Homeschooling Pena Surabaya - Hidayah, Lailatul Nur; Yulianingsih, Wiwin (Jurusan Pendidikan Luar Sekolah Fakultas Ilmu Pendidikan UNESA, 2024)
This research aims to examine the relationship between family support and learning motivation of Package B students at Homeschooling Pena Surabaya. Family support is an important factor that can influence student learning motivation, especially in a homeschooling environment which requires active involvement from parents and other family members. This research uses quantitative methods with a correlational approach. Data collection techniques used questionnaires and documentation with research respondents in grades VII, VIII and IX. The data analysis technique uses the Pearson Product formula. The results of the research show that there is a positive or unidirectional relationship between the variables of family support and learning motivation in package B students at Homeschooling Pena Surabaya, which is indicated by the significance value between family support and learning motivation is 0.010. This means the significance value is smaller than 0.05 (0.010 < 0.05). These findings show that the higher the support provided by the family, the higher the students' learning motivation.